Prevalence of hypertension and its associated risk factors during COVID-19 pandemic in the capital of Bangladesh - Urmila Roy; Arafat Hassan Razon; Tanvir Ahmad; Tabassum Sultana Barsha (Human Nutrition & Metabolism)
Background: Hypertension (HTN) has emerged as a significant public health challenge and a leading cause of mortality and morbidity in developing countries like Bangladesh. Objective: This study aimed to assess the prevalence of hypertension and its associated risk factors among residents of Dhaka, the capital of Bangladesh, during the COVID-19 pandemic. Methods: A cross-sectional study was conducted using a multistage random sampling technique to select 305 individuals from Khilkhet Thana in Dhaka North City Corporation. Data were collected through direct surveys using a modified version of the WHO STEPS questionnaire and analyzed using SPSS version 22 software. Findings: The study identified a 34.4 % prevalence of HTN among the participants, with 46.2 % of hypertensive individuals being under 40 years of age. Of the 105 hypertensive individuals, 65 % were newly diagnosed during the study, and 11 previously diagnosed individuals were not on any medication. A significant association (P < 0.001) was observed between the prevalence of HTN and inadequate intake of fruits (OR = 3.129, 95 % CI = 1.912–5.122, χ2 = 21.328), insufficient vegetables consumption (OR = 2.199, 95 % CI = 1.356–3.565, χ2 = 10.373), high intake of fatty foods (OR = 2.387, 95 % CI = 1.465–3.890, χ2 = 12.454), and excessive salt consumption (OR = 2.771, 95 % CI = 1.677–4.579, χ2 = 16.310). Additionally, the prevalence of HTN was notably higher among overweight (46.70 %) and at-risk (22.90 %) individuals, based on Body Mass Index (BMI) and waist-to-hip ratio (WHR), respectively. The study also found significant correlations (P < 0.001) between HTN and factors such as smoking (OR = 2.824, 95 % CI = 1.601–4.980, χ2 = 13.432), kidney disease (OR = 7.534, 95 % CI = 2.694–21.070, χ2 = 19.282), general stress (OR = 3.692, 95 % CI = 2.179–6.255, χ2 = 24.896), COVID-19 related stress (OR = 3.511, 95 % CI = 2.116–5.826, χ2 = 24.712) and sleeping pattern (OR = 5.798, 95 % CI = 3.404–9.875, χ2 = 45.724). Conclusions: The high prevalence of HTN, particularly among younger individuals during the COVID-19 pandemic, highlights the urgent need for nationwide surveys, surveillance, and clinical research to accurately depict the true burden of HTN in Bangladesh.